Uji Efektivitas Pupuk Organik Cair (POC) Pada Pertumbuhan Tanaman Kacang Panjang (Vigna sinensis L.) - Souwardi, Taufan Wendra; Rahmi, Hayatul; Saputro, Nurcahyo Widyodaru (JURNAL AGROPLASMA, 2023)
Nutrients is a major determinant in the production and growth rates of plants can be increased by fertilizer delivery. The main ingredient of organic fertilizers is organic matter, which has been altered by decomposing bacteria to produce components that can be used by plants without contaminating soil or water. The nutrients required by plants are absorbed through the roots of the soil. The purpose of this study is to find the best effectiveness and dosage of fertilizer feeding on the growth of long bean plants. Single-factor Randomized Design (RAK) with 5 repeaters was the method in this study. There are 8 treatments consisting of controls, POC Household Organic Waste (100 ml/l, 200 ml/l, 300 ml/l, 400 ml/l and 500 ml/l), POC NASA and NPK with different doses. The results of the study showed clear differences between treatment fertilizers. Treatment A7 (NPK) is the best treatment with a plant height of 56.72 cm and a leaf count of 17.08 at 21 days after planting.Â Keywords: Organic Waste, Liquid Organic Fertilizer, Long BeansÂ